(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
National healing and reconciliation have become integral engagements in post-conflict recovery processes in Africa. However, the persistence of violent conflicts has cast doubts on the extent to which governments can facilitate reconciliation. Unless a deliberate effort is made to incorporate peace education through the lens of ‘difficult history’, the cycles of ethnic violence characterising post-colonial Zimbabwe will continue unabated. This study examines how the Zimbabwe government can navigate social conflicts and contribute to building democratic peace and security through public education. The Gukurahundi massacre is considered pivotal towards understanding how ‘difficult history’ can be utilised to promote healing and reconciliation in a state with perennial ethnic antagonism. An argument is sustained that educational institutions have the capability of transforming the pervasive atmosphere of suspicion, mistrust and discord between the Ndebele and the Shona for national healing and reconciliation.